Symptoms and signs: physical disease or illness behaviour?. Issue 6447 (22nd September 1984) - Waddell, G; Bircher, M; Finlayson, D; Main, C J
Abstract : The amount of treatment received by 380 patients with backache was found to have been influenced more by their distress and illness behaviour than by the actual physical disease. Patients showing a large amount of inappropriate illness behaviour had received significantly more treatment (p less than 0.001). The symptoms and signs of illness behaviour need to be clearly distinguished from those of physical disease, and better assessment of illness behaviour is essential if everyday clinical practice is to fulfil the ideal of treating patients as well as diseases.